Antihypertensive effects of D-polymannuronic sulfate and its related mechanisms in renovascular hypertensive rats - Zhu Hai-Bo; Geng Mei-Yu; Guan Hua-Shi (Acta Pharmacologica Sinica, 2016)
"AIM: To investigate the antihypertensive effects of D-polymannuronic sulfate (DPS), a kind of sulfated polysaccharide, and the underlying mechanisms in renovascular hypertensive rats (RHR). METHODS: Used two-kidney one clip (Goldblatt, 2-K 1C) method to produce RHR model. DPS was given i.v. or ig for 5 wk with the initiation of establishment of RHR. Serum nitric oxide (NO) was determined with NO kit; plasma angiotensin II (Ang II) and endothelin-1 (ET-1) were measured by radioimmumoassays. RESULTS: In acute therapeutic experiments, DPS markedly reduced systolic blood pressure (SBP) and diastolic blood pressure (DBP) dose-dependently and decreased heart rate (HR) with reduction in arterial blood pressure. In the prophylactic experiments, DPS prevented the rise in SBP and DBP in a dose-dependent manner. The hypotensive potency of DPS 50 mg/kg is comparable to that of captopril (14 mg/kg). Moreover, DPS elevated serum NO contents and lowered plasma concentrations of Ang II and ET-1. CONCLUSION: The antihypertensive activities of DPS might be involved both in increasing the generation of nitric oxide and in decreasing the production of angiotensin II and endothelin-1 in vivo."